Tren Perceraian Karena Financial Independence Istri: Analisis Maqasid Syariah dan Teori Keadilan Gender - Naela Rosita; Nafiah Wachidlatul Jannah (Maqasid: Jurnal Studi Hukum Islam, 2026)
Divorces in Indonesia continues to rise year after year. Many of these divorce lawsuits are filed by wives. One factor that motivates a wife to file for divorce from her husband is her financial independence. When a wife is financially stable, she is no longer dependent on her husband. Therefore, if the husband commits an act that violates the marriage, the wife can easily decide to end the marriage. This study aims to determine the factors causing divorce among financially independent wives, the concept of maqasid sharia in divorce decisions filed by wives, and the rights of wives after divorce from a gender justice perspective. This study is a normative study with a conceptual and case approach. The results show that factors that make financially independent wives easily choose to divorce include the wife's lack of financial dependence, the hope of having equal family relationships, and a high awareness of fighting for her dignity and honor. From the perspective of maqasid sharia, divorce can be a means to maintain the dignity, emotional health, and moral safety of women. According to the theory of gender justice, a wife who is financially independent still has the right to post-divorce rights because the essence of justice is not whether a woman is economically capable or not, but rather the fulfillment of responsibilities and relational respect.  The implications of this research suggest that a wife's financial independence should not be understood as a threat to the integrity of the marriage, but rather as a protection of the maqasid sharia and the enforcement of gender justice in marital and post-divorce relationships. Keywords: Divorce, Financial Independence, Maqasid Syariah, Gender Justice, Women's Rights.